Exploring the tendency to avoid physical activity and sports in university students / Emelly Wendy Islee and Patricia Pawa Pitil - Islee, Emelly Wendy; Pitil, Patricia Pawa (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Physical inactivity significantly contributes to the onset of noncommunicable diseases (NCDs) such as cardiovascular disease, diabetes, and obesity, and is a major factor in global mortality rates. University students, particularly those aged 20–29, exhibit higher rates of inactivity compared to other age groups, largely due to factors such as body dissatisfaction, health awareness, and life transitions [1]. These students often face shifts in lifestyle habits as they transition from adolescence to adulthood, which can impact their physical activity levels. Academic pressures, changes in social environments, and evolving body image concerns can contribute to a decrease in physical activity. This study examines the differences in the tendency to avoid physical activity and sports (TAPAS) across gender, age groups, and body mass index (BMI), providing valuable insights into the patterns and motivations that influence students’ engagement in physical activity.